Impact of Postoperative Infectious Complications on Long-Term Outcomes for Patients Undergoing Simultaneous Resection for Colorectal Cancer Liver Metastases: A Propensity Score Matching Analysis - Chen, Qichen; Deng, Yiqiao; Chen, Jinghua; Zhao, Jianjun; Bi, Xinyu; Zhou, Jianguo; Li, Zhiyu; Huang, Zhen; Zhang, Yefan; Chen, Xiao; Zhao, Hong; Cai, Jianqiang (Frontiers in Oncology, 2022)
Abstract Objective: To investigate the impact of postoperative infectious complications (POI) on the long-term outcomes of patients with colorectal cancer liver metastasis (CRLM) after simultaneous resection of colorectal cancer and liver metastases. Methods: Four hundred seventy-nine CRLM patients receiving simultaneous resection between February 2010 and February 2018 at our hospital were enrolled. A 1:3 propensity score matching analysis (PSM) analysis was performed to balance covariates and avoid selection bias. After PSM, 90 patients were distributed to the POI group, and 233 patients were distributed to the no POI group. A log-rank test was performed to compare the progression-free survival (PFS) and overall survival (OS) data. A multivariate Cox regression model was employed to identify prognostic factors influencing OS and PFS. A value of two-sided P<0.05 was considered statistically significant. Results: Compared to patients in the no POI group, patients in the POI group were more likely to have hepatic portal occlusion (78.9% vs. 66.3%, P=0.021), operation time ≥325 min (61.1% vs. 48.1%, P=0.026), and intraoperative blood loss ≥200 ml (81.1% vs. 67.6%, P=0.012). In multivariate analysis, intraoperative blood loss ≥200 ml (OR = 2.057, 95% CI: 1.165-3.634, P=0.013) was identified as the only independent risk factor for POI. Patients with POI had a worse PFS (P<0.001, median PFS: 7.5 vs. 12.7 months) and a worse OS (P=0.010, median OS: 38.8 vs. 59.0 months) than those without POI. After 1:3 PSM analysis, no differences in clinicopathologic parameters were detected between the POI group and the no POI group. Patients with POI had a worse PFS (P=0.013, median PFS: 7.5 vs. 11.1 months) and a worse OS (P=0.020, median OS: 38.8 vs. 59.0 months) than those without POI. Multivariate analysis showed that POI was an independent predictor for worse PFS (HR=1.410, 95% CI: 1.065-1.869, P=0.017) and worse OS (HR=1.682, 95% CI: 1.113-2.544, P=0.014). Conclusions: POI can significantly worsen the long-term outcomes of CRLM patients receiving simultaneous resection of colorectal cancer and liver metastases and should be considered to improve postoperative management and make better treatment decisions for these patients.